With every great breath : new and selected essays, 1995-2023 - Bass, Rick, 1958- (Counterpoint, 2024)
"For acclaimed writer and environmental activist Rick Bass, it can be wearying to dwell relentlessly upon the broken, the fragmented, the dead and dying and doomed to extinction. Activism is a necessary part of the environmental movement, but so is the time-honored celebration of the beauty that inspires us. Spanning his storied career, these new and selected essays attempt to take a brief step to the side, away from lamentation and prescription, to inhabit, as deeply as possible, the greater depths of the beauty in each moment. Throughout, Bass offers a portrait of our planet that is always alert to its wonders, even in the face of environmental crisis"--